Advances in molecular mechanisms underlying cadmium uptake and translocation in rice - Ai, Hao; Wu, Daxia; Li, Chunli; Hou, Mengmeng (Frontiers in Plant Science, 2022)
The increasing cadmium (Cd) pollution in paddy fields has severely threatened China’s ecological and food safety. Cultivation of low Cd accumulation varieties to reduce Cd content in rice or cultivation of Cd-tolerant varieties for phytoremediation are considered effective methods to control Cd pollution in paddy fields. However, the underlying molecular mechanism of Cd absorption and transport by rice plants needs to be deciphered to cultivate these varieties. Here, we summarized the molecular mechanisms underlying Cd absorption and transport in rice, as well as the variation of Cd accumulation among rice varieties, the QTLs related to Cd accumulation in rice, and discusses the direction of future research.